The use of marijuana in the treatment of Parkinson's Syndrome (Research, Society and Development, 2022)
The neurological, chronic and progressive disease known as Parkinson's Syndrome is associated with the constant loss of brain cells that produce the neurotransmitter dopamine, responsible for carrying information to the body. Pharmacotherapy of Parkinson's disease is aimed at controlling symptoms, not completely preventing disease progression; although there is no cure for this syndrome, several palliative treatment methods are available, among them, drug therapy has been shown to be effective. As a healthy and natural alternative, Cannabis sativa shows promising results, especially in cases of chronic pain. Cannabis is among the oldest plants cultivated by man, with archaeological and historical indications; and that the cultivation of the plant was also intended for the extraction of industrial products such as the fibers used in the ropes of boats. Currently, research indicates the therapeutic use of a small number of its active principles with promising results that are being scientifically tested and proven for the treatment of syndromes and/or diseases.